2018
DOI: 10.3389/fimmu.2018.03030
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role for PD-1:PD-L1 as Mediator of Pulmonary Vascular Endothelial Cell Functions in Pathogenesis of Indirect ARDS in Mice

Abstract: Deficiency of the co-inhibitory receptor, Programmed cell death receptor (PD)-1, provides a survival benefit in our murine shock/sepsis model for the development of indirect acute respiratory distress syndrome (iARDS). Further, of clinical significance, patients that develop ARDS express increased PD-1 on their blood leukocytes. While PD-1 expression and its regulatory role have been associated with mainly T-cell responses, the contribution of its primary ligand, PD-L1, broadly expressed on non-immune cells su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 54 publications
1
40
1
Order By: Relevance
“…Indeed, the expression of ZO-1 is highly regulated by undisturbed VE cadherin molecules [98,99]. In line with this, a loss of VE cadherin expression and ZO-1 occurred on the ECs monolayers with PD-L1 sufficiency [89], whereas the levels of the junctional molecules were shown to be intact even with TNF-α stimulation under PD-L1-deficient conditions, implying an uprooting quality of PD-L1 on EC-associated vascular barrier integrity.…”
Section: Relevance Of Pd-l1/pd-1 Axis On Vascular Endothelium and Barmentioning
confidence: 55%
See 2 more Smart Citations
“…Indeed, the expression of ZO-1 is highly regulated by undisturbed VE cadherin molecules [98,99]. In line with this, a loss of VE cadherin expression and ZO-1 occurred on the ECs monolayers with PD-L1 sufficiency [89], whereas the levels of the junctional molecules were shown to be intact even with TNF-α stimulation under PD-L1-deficient conditions, implying an uprooting quality of PD-L1 on EC-associated vascular barrier integrity.…”
Section: Relevance Of Pd-l1/pd-1 Axis On Vascular Endothelium and Barmentioning
confidence: 55%
“…Though the nuclear accumulation of FoxO1 is needed for the sustained expression of PD-1 and for the survival of PD-1 high CD8 + -exhausted T cells [108], the relationship between FoxO1 and PD-L1 remains obscure and is not yet reported. Surprisingly, the endothelial cell release of ang2 was significantly reduced in thrombin and TNF-α-stimulated PD-L1 -/-EC monolayers [89], signifying a novel and indirect link of the endothelial cell regulation of PD-L1 by ang2 at the gene level, which requires further investigations. This could be well corroborated with another cell type, where excessive serum-circulating ang2 fosters the upregulation of PD-L1 on M2-type macrophages [109].…”
Section: Relevance Of Pd-l1/pd-1 Axis On Vascular Endothelium and Barmentioning
confidence: 94%
See 1 more Smart Citation
“…(1) Overexpressing TGFβ1 inhibited the proliferation of mMSCs during days 5-7 but had no effect on their differentiation or migration. 2 As an important part of adaptive immunity, T cell immunity is involved in the development of ARDS 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that speci c regulation of T cell differentiation could improve the immunity and in ammation state of ARDS in animal models, resulting in prognosis improvement 21,23,24 . It was also found in our study that the regulation of T cell differentiation in patients with community-acquired pneumonia was directly related to their prognosis 25 .…”
Section: Discussionmentioning
confidence: 99%